Palaeomagnetism of Dyke swarms from the deccan volcanic province of India - Prasad, J. N.; Patil, S. K.; Saraf, P. D.; Venkateshwarlu, M.; Rao, D. R. K. (My University, 1996)
Palaeomagnetic results of 19 dykes situated south of Narmada river (21°30'N, 74°15'E) in Dhule district of the Maharashtra state, India are reported. Of the 19 dykes, 11 dykes exhibit a normal magnetic polarity, and 4 dykes a reverse polarity. The remaining 4 dykes yielded mostly scattered and unstable sample directions. The normal and reverse directions are almost antipodal. The characteristic remanence is indicated to reside in magnetite, and is most probably primary. The N-Pole position corresponding to the mean directions of 11 dykes (7 normal and 4 reversed) based on a minimum of 4 sample characteristic directions per dyke is at 37.2°N, 80.5°W (A95=9.7°). This pole is concordant with the Deccan Superpole, indicating a similar age of magnetization for the Deccan basalt flows and the dykes intruding them. A joint consideration of similarity of palaeopoles of the dykes and the lava flows, magnetic polarity of dykes, and their stratigraphic positions of intrusions in the lava flow sequence support the view that the volcanic activity in the Deccan area spanned a short duration. The post-trappean tectonic activity resulting in the dyke swarms may possibly have coincided with the opening of the Arabian Sea and the rifting of the Seychelles-Mascarene oceanic plateau.
Keywords: Palaeomagnetism; Dyke swarms; Deccan volcanic province (DVP)